2013
DOI: 10.1186/1471-2164-14-751
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and metabolomic profiles of larval hemolymph associated with diapause in the cotton bollworm, Helicoverpa armigera

Abstract: BackgroundDiapause is programmed developmental arrest coupled with the depression of metabolic activity and the enhancement of stress resistance. Pupal diapause is induced by environmental signals and is prepared during the prediapause phase. In the cotton bollworm, Helicoverpa armigera, the prediapause phase, which contains two sub-phases, diapause induction and preparation, occurs in the larval stage. Here, we performed parallel proteomic and metabolomic analyses on H. armigera larval hemolymph during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 55 publications
10
41
0
3
Order By: Relevance
“…Notably, the levels of ferritin were increased in the entire summer diapausing process. Ferritin has been associated with a stress response in early diapause of N. vitripennis (Wolschin & Gadau, ) and Helicoverpa armigera (Zhang et al ., ). As an important ion protein, the accumulation of ferritin in SD can prevent destructive oxidative stress triggered by free iron.…”
Section: Resultsmentioning
confidence: 97%
“…Notably, the levels of ferritin were increased in the entire summer diapausing process. Ferritin has been associated with a stress response in early diapause of N. vitripennis (Wolschin & Gadau, ) and Helicoverpa armigera (Zhang et al ., ). As an important ion protein, the accumulation of ferritin in SD can prevent destructive oxidative stress triggered by free iron.…”
Section: Resultsmentioning
confidence: 97%
“…These include glutathione S-transferase (GST) with antioxidant activity, protecting cellular components from oxidative damage. Ferritin is one of the most abundant proteins in dormant RE and E0 and shows higher abundance in diapausing insects (123,124) and copepods (125). It has been shown that the concentration of ferritin increases in response to stresses such as anoxia (126).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90, known to bind steroid receptors and kinases, diminishes and may reflect low ecdysteroid levels (99). Metabolomic and proteomic analyses show that the larval brain and hemolymph of the cotton bollworm, Helicoverpa armigera, upon induction of and preparation for diapause, display several regulatory proteins and biochemical changes, but no HSPs are observed at this early prediapause stage (100,101), as is true for the Asian tiger mosquito, Aedes albopictus, as it prepares for adult reproductive diapause (68). Hsp20.7 and Hsp90 decline in the brain during diapause of H. armigera, while Hsp21.4 rises (13, 60), as does Hsp70 mRNA (4).…”
Section: Hsps In Insect Prepupae and Pupae During Diapausementioning
confidence: 96%